Islamic Believable: Water as a Perfecting to Prayer and as a Community Empowerment of Islamic Da'wah - A'yun, Annisa Qurrota; Ediyono, Suryo; Keulen, Marijke Van; Dorani, Abdulaziz (Ijtimā iyya Journal of Muslim Society Research, 2024)
This paper will discuss the relationship between water and the propagation of Islam in the community as a form of realization of Islamic philanthropic funds because BMH utilizes philanthropic funds as a water source procurement program. The object of observation in this paper is the Baitul Maal Hidayatullah Amil Zakat Institution, representative of East Java Province, which carries out a drilled well program for the community. A literature review was carried out on knowledge books and scientific articles explaining beliefs and water in Islam. Results of the discussion: Water is a source of human life and is included in the primary needs of Islam. BMH is one of the institutions that consists of a water supply program to become a process of preaching to the community through the drilled well program. Assistance with drilled wells to the community, mosques, and Islamic boarding schools has become a door to da'wah in the area because by helping with water supplies, it can bring the BMH Institution closer to the community so that the community is willing to open itself up to learn more about BMH and the Islamic religion.